1983
DOI: 10.2307/3575863
|View full text |Cite
|
Sign up to set email alerts
|

X-Irradiation Effect on Human Red Cells: Hemoglobin Study by Mössbauer Spectrometry

Abstract: This work is a study of the radioinduced transformations undergone by intraglobular hemoglobin. Mössbauer spectrometry allows us to study in a wide range of doses the effect of X rays on deoxyhemoglobin as well as on oxyhemoglobin. Using this technique we have shown large differences between these two derivatives of hemoglobin. Deoxyhemoglobin leads to the formation of only one ferric nonheme compound while oxyhemoglobin produces this same compound as a last step after intermediary production of deoxyhemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Because of the significant proportion of units that are being leucoreduced today, it is important to evaluate this process in further studies of X‐ray irradiation, and at 35 Gy of gamma irradiation. Both X‐ray and gamma irradiation have been reported to decrease RBC permeability [11,12], and X‐ray irradiation has been reported to affect changes in methaemoglobin formation [13]. These parameters were not assessed in this study, and may not have much clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the significant proportion of units that are being leucoreduced today, it is important to evaluate this process in further studies of X‐ray irradiation, and at 35 Gy of gamma irradiation. Both X‐ray and gamma irradiation have been reported to decrease RBC permeability [11,12], and X‐ray irradiation has been reported to affect changes in methaemoglobin formation [13]. These parameters were not assessed in this study, and may not have much clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that earlier study of oxyhemoglobin in red blood cells exposed to X-rays by Mo ¨ssbauer spectroscopy showed oxyhemoglobin deoxygenation while protein destruction led to formation of two species: a hemochrome-like compound and a non-heme Fe(III) compound that was considered as a final product of protein destruction. 48,49 Mo ¨ssbauer spectra of oxyhemoglobin exposed to microwave heating (2.45 GHz, 900 W) for 5 and 15 s demonstrated an increase of oxyhemoglobin spectral line width and the formation of a ferric compound. 46 Mo ¨ssbauer parameters of oxyhemoglobin subspectra revealed almost the same values of DE Q and d as those for a non-irradiated oxyhemoglobin sample.…”
Section: Environmental Factorsmentioning
confidence: 97%
“…Mössbauer spectroscopy can be used to investigate some molecular mechanisms of biological effects of exogenous agents. The study of deoxy-and oxyhemoglobin irradiated by X-rays identified iron containing compounds resulting from radiolysis of proteins and showed differences of both hemoglobin forms destruction [52,53]. Another study of oxyhemoglobin radiolysis demonstrated the formation of different products of protein damage by γ-rays of various energies, by electrons and by microwave heating [54][55][56][57][58].…”
Section: Study Of the Effect Of Environmental Factorsmentioning
confidence: 99%